2021
DOI: 10.15170/tvt.2021.06.04.05
|View full text |Cite
|
Sign up to set email alerts
|

A vendégelégedettség és a jövedelmezőség, mint sikertényezők kapcsolatának vizsgálata a magyarországi négycsillagos hotelek esetében

Abstract: A szállodai szálláshely-szolgáltatás minősége és a vendégelégedettség mint kulcsfontosságú tényezők az elmúlt évtizedekben a szállodák sikerességének alapvetően meghatározó elemei lettek. Hazai vonatkozásban egyedi az olyan kutatás, amely vizsgálja az egyes hotelek vendégelégedettsége és jövedelmezősége közötti kapcsolatot. A COVID-19 pandémia tükrében megállapítható, hogy a pénzügyi mutatók szállodaigazgatók számára is legalább olyan súlyúak, mint a világjárványt és válságot megelőző időszakban. Ugyan a kutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The calorific value of wood bark biomass ranges from 15 to 23 MJ•kg −1 , depending on the species evaluated [12][13][14]. Many researchers have shown that bark has a higher heating value than wood [15][16][17][18][19][20]. According to Lykidis et al [15] and Szyszlak-Bargłowicz et al [21], the differences are associated with the presence of a high amount of ash in bark and the increased loss of volatile compounds during its drying [15].…”
Section: Introductionmentioning
confidence: 99%
“…The calorific value of wood bark biomass ranges from 15 to 23 MJ•kg −1 , depending on the species evaluated [12][13][14]. Many researchers have shown that bark has a higher heating value than wood [15][16][17][18][19][20]. According to Lykidis et al [15] and Szyszlak-Bargłowicz et al [21], the differences are associated with the presence of a high amount of ash in bark and the increased loss of volatile compounds during its drying [15].…”
Section: Introductionmentioning
confidence: 99%